Municipal infrastructure policies in the Federal Republic - In between growing disparities and losing political autonomy? - (:unkn) unknown (Wiley, 2017)
Drawing from Scharpf's joint decision making approach and his concept of the joint decision trap, the following paper researches the development of municipal infrastructure investment in relation to the overall financial situation. The analyzed data are being provided by a representative panel survey among 4,000 German municipalities conducted in 2016 by the German Institute of Urban Affairs. The starting point of the analysis is the description of a dilemma: Growing financial disparities between the municipalities and a loss-making infrastructure of many cities and towns leads to an institutionalization of a growing number of grant programmes and forms of mixed financing. These programmes do not provide adequate solutions for the heterogeneity of municipal needs. By neglecting their individual needs they cannot take into account the growing disparities of municipal financial situations. Rather, they produce an institutional setting, which fosters sub-optimal policy-outcomes and is resilient to changes.
Keywords: Gemeinde; Infrastrukturbedarf; Infrastrukturkosten; Kommunalinvestition; Investitionsbedarf; Investitionsförderung; Förderungsprogramm; Wirkungsanalyse; Mischfinanzierung